If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 7 = 1 + -2x Reorder the terms: 7 + 4x = 1 + -2x Solving 7 + 4x = 1 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 7 + 4x + 2x = 1 + -2x + 2x Combine like terms: 4x + 2x = 6x 7 + 6x = 1 + -2x + 2x Combine like terms: -2x + 2x = 0 7 + 6x = 1 + 0 7 + 6x = 1 Add '-7' to each side of the equation. 7 + -7 + 6x = 1 + -7 Combine like terms: 7 + -7 = 0 0 + 6x = 1 + -7 6x = 1 + -7 Combine like terms: 1 + -7 = -6 6x = -6 Divide each side by '6'. x = -1 Simplifying x = -1
| 9x+4=x+36 | | 12x+32=6+x | | 5-8x=0 | | 7x-10=6+5x | | (1+bx)(1+6ax)=1+20x+171x^2 | | -4c+6u=6 | | 29/87 | | 9m/11=18 | | 51-2x=9-8x | | 69+(2x-1)=90 | | 8x-2+4x+10=3+2x+x+20 | | 12x+25=3x+151 | | 2x+12=3x-12 | | X-x-10=0 | | x^2-2*x+y-4*y+5=0 | | 2+12=3-27 | | x+70=x^3-39x+70 | | 2x-3+4x-5= | | x^3-39+70=o | | 2(3b+7)=4 | | (x/3)*x=6250 | | 4+3x=-8+x | | 19-5x=7-8x | | 5/9*18= | | 5(wx-v)=9(x+v) | | 3x+6=18-3x | | 62=8m+6 | | X^2-62x+672= | | 2+5x=-2+x | | X^2+62x+672= | | (2x+1)(2x-1)=99 | | 4n+20=n+40 |